2005
DOI: 10.1158/0008-5472.can-05-0011
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Profiling of Engineered Mouse Melanomas with Manipulated Histamine Production Identifies Histamine H2 Receptor and Rho-C as Histamine-Regulated Melanoma Progression Markers

Abstract: In the present study, the impact of acquired neoplastic L-histidine decarboxylase (HDC) expression, and its direct consequence, the release of histamine in the tumor environment, was assessed on melanoma tumor progression. B16-F10 mouse melanoma cells were manipulated via stable transfection, and nine novel transgenic variants were generated in triplicates, constitutively expressing the full-length sense mouse HDC mRNA, a mock control, and an antisense HDC RNA segment, respectively. Establishing both primary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…A recent research conducted by Noelia and coworkers has concluded the exhibition of antitumor effect of histamine in vitro and in vivo on human melanoma, suggesting histamine as a potential therapeutic compound for the treatment of malignant melanoma (Massari et al 2013). Significant elevation of histamine in melanoma group observed in this study may be a result of up-regulation of histidine decarboxylase expression caused by metastatic melanoma in spleen, which is consistent with previous reports where B16F10 mouse melanoma cells show a rising level of histamine compared with normal melanocytes (Pos et al 2005; Davis et al 2011; Gruetter et al 2009; Gruetter et al 2008). Alanine is most commonly produced from pyruvate via alanine transaminase.…”
Section: Resultssupporting
confidence: 92%
“…A recent research conducted by Noelia and coworkers has concluded the exhibition of antitumor effect of histamine in vitro and in vivo on human melanoma, suggesting histamine as a potential therapeutic compound for the treatment of malignant melanoma (Massari et al 2013). Significant elevation of histamine in melanoma group observed in this study may be a result of up-regulation of histidine decarboxylase expression caused by metastatic melanoma in spleen, which is consistent with previous reports where B16F10 mouse melanoma cells show a rising level of histamine compared with normal melanocytes (Pos et al 2005; Davis et al 2011; Gruetter et al 2009; Gruetter et al 2008). Alanine is most commonly produced from pyruvate via alanine transaminase.…”
Section: Resultssupporting
confidence: 92%
“…HA may promote the proliferation of NSCs and cancer stem cells (Pós et al 2005;Molina-Hernandez and Velasco 2008). In contrast, Medina et al (2009) showed that HA impairs the proliferation of human malignant melanoma cells, probably by increasing hydrogen peroxide levels.…”
Section: Histamine Effects On Neural Stem Cellsmentioning
confidence: 98%
“…HA may promote the proliferation of NSCs and cancer stem cells (Pós et al. 2005; Molina‐Hernandez and Velasco 2008).…”
Section: Histamine and Cns Developmentmentioning
confidence: 99%
“…On one side, the use of specific anti-sense oligonucleotides against histidine decarboxylase (HDC) decreased the proliferation rate of human melanoma cells [11], while over-expression of HDC markedly accelerates tumor growth and increases metastatic colony-forming potential in mouse melanoma [12, 13]. On the other side, it was demonstrated by using histamine agonists, antagonists and genetic tools, that histamine treatment produced an inhibitory effect on proliferation mediated in part through the stimulation of the H 4 R in WM35 and M1/15 human melanoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Histamine dihydrochloride inhibits the formation of reactive oxygen species from monocytes/macrophages by suppressing the activity of NADPH oxidase, and thus preventing the inactivation of T cells and NK cells [15]. In addition, it is not possible to discard a direct action of histamine on melanoma cells, considering that the expression of H 1 R, H 2 R, H 3 R and H 4 R in human melanoma cell lines was shown [8, 12, 16]. In addition, literature suggests that those with allergy have a reduced risk of developing cancer versus the general population [17] and that a history of asthma may be a protective factor in cutaneous melanoma [18].…”
Section: Introductionmentioning
confidence: 99%